Structural studies of peptide binding to chicken class I MHC molecules, the CD6-CD166 interaction and enzymes involved in bacterial sulfur metabolism - Chappell, P (2015)
T cell activation is critical for the initiation of the adaptive immune response against both pathogens and malignant cells. This process depends on a complex set of finely tuned interactions, not only between the T cell receptor (TCR) and peptide-MHC complexes, but also between numerous accessory molecules. Chapter 2 of this thesis examines CD6, a transmembrane glycoprotein predominantly found on the surface of T cells, and its interaction with CD166, another transmembrane glycoprotein found on the surface of antigen presenting cells (APCs), amongst others. This interaction is required for optimal T cell activation. I have solved the X-ray crystal structures of the three extracellular SRCR domains of CD6 and the two membrane distal IgSF domains of CD166. In collaboration with colleagues, the ligand binding sites on both CD6 and CD166 have been further defined. We have also shown that a single nucleotide polymorphism (SNP) in CD6 caused glycosylation, hindering the CD6/CD166 interaction. Finally, native mass spectrometry revealed competition between the heterophilic CD6/CD166 interaction and the homophilic CD166 interaction.